The rain forest treasure house of biodiversity - Johnson, Julie
Once covering about a fifth of the world's land surface, the species-rich rain forests now compose only seven percent, and the exploitation of these fascinating areas threatens the gene pool of the entire planet. The learning objectives for this programme are : 1) Conditions needed for the creation and continuation of rain forests will be identified, and we'll see how plants and animals live within the different elevations of a rain forest's canopy. 2) Students will be able to locate and distinguish the world's various rain forests and to discuss the dangers that face these regions because of rampant development 3) The idea of biodiversity will be discussed and its importance to the world's ecosystem will be explained.